The Réunion Subchron vegetation and climate history of the northeastern Russian Arctic inferred from the Lake El'gygytgyn pollen record - Zhao W.; Andreev A.; Wennrich V.; Tarasov P.; Anderson P.; Lozhkin A.; Melles M. (2015)
© 2015 Elsevier B.V. The 318-m-thick sediment record from Lake El'gygytgyn provides unique opportunities for a detailed examination of environmental changes during the Réunion Subchron polarity reversal event (2.1384-2.1216. Myr. BP) in the northeastern Russian Arctic. The paper describes vegetation and climate fluctuations between ~. 2.15 and 2.10. Myr. BP as inferred from palynological data. Biome reconstructions indicate that throughout this interval the tundra (TUND) biome generally has higher affinity scores as compared to cold steppe (STEP) or cold deciduous forest (CLDE). An exception is the climatic optimum between ~. 2.139 and 2.131. Myr. BP, coinciding with Marine Isotope Stage 81 (approximately the Réunion Subchron), when the CLDE biome has the highest scores. Landscape-openness indices suggest that more closed vegetation characterized most of the interval between 2.146 and 2.127. Myr. BP, when deciduous forest and shrubs expanded in the regional vegetation and climate was relatively warm and wet. Peaks in green algal colonies (Botryococcus) and Zygnema-type spores ~. 2.150-2.146, ~. 2.131-2.123, and ~. 2.112-2.102. Myr. BP indicate expansions of shallow-water habitats and lowered lake levels. Comparisons with biome reconstructions from other interglacial intervals at Lake El'gygytgyn suggest that precession-related summer insolation intensity and obliquity-related duration of summer daylight are major controls on the onset of interglaciations, whereas obliquity probably plays a more significant role on vegetation succession at northern high latitudes during the Pleistocene.